Benalu as a Material for the Creation of Three-Dimentional Fine Art Works - Zaini, Imam; Mutmainah, Siti; Ardani, Muhammad Widyan; Li, Chaoqun (Proceeding of International Joint Conference on UNESA, 2024)
In Unesa’s visual arts education programme, all students must take the 3-Dimensional Basic Art course as a basic art course. The benalu tree as an alternative material to create 3- dimensional works of art. The objectives of this research are: (1) to describe the process of making 3-dimensional artworks from benalu material (2) to create 3-dimensional artworks from benalu material. Benalu has various shapes and sizes, so it is relatively easy when used to create 3-dimensional works of art, both in the direction of pure art and applied art. This research uses the creative method of ’Design Thinking’ (Hendriyana, 2022) through exploration and experimentation of materials, shapes, sizes, techniques and construction. This research refers to the form of art practice led research conducted by students of the fine arts education programme class of 2022. The results of the research are; (1) the process of making works by preparing tools consisting of ladders, axes, saws, knives, sickles/clurit, ropes, and poles. Necessary materials, benalu, wood glue, wood politur, water, cotton, wood sandpaper, cloth, clear paint. (2) Created 4 3-dimensional artworks with the titles ’Parasite’ (Berliana Ayomi), ’Animal’ (Cyiko Felicia), ’Mushroom’ (Diana Bella), ’Dancing’ (Lucky Gozali).